Hepatitis C virus infection in health-care settings: Medical and ethical implications - Francisco Javier Bosques-Padilla, M.D.; Genaro Vázquez-Elizondo; Ana Villaseñor-Todd; Elvira Garza-González; José Alberto Gonzalez-Gonzalez; Héctor Jesús Maldonado-Garza (Annals of Hepatology, 2010)
Hepatitis C is a major public health issue. It infects about 200 million people worldwide and is a major cause of chronic liver disease. Its transmission in medical facilities is a topic of increased concern, as outbreaks of the disease had raised the attention of media and medical authorities. To date, evidence suggests that infection from in which a health-care worker is involved is mostly result of bad injecting practices as well as the result of shared medical devices. Furthermore, the infection caused by physicians is rare and very few well documented cases exist on the literature. Among countries, different definitions and legislation exist, in that mode that the responsibility of this issue almost is a an obligation of individual institutions. Nonetheless, Hepatitis C virus transmission in medical facilities is an important source of new cases, and as treatments options are very limited, its recommendable that institutions as well as governments implement policies to avoid Hepatitis C spread in a almost fully preventable setting.